Precisão de coordenadas planimétricas obtidas com receptores GNSS de pontos situados sob redes elétricas de alta tensão - Hillebrand, Fernando Luis (2012)
The purpose of this work was investigate and measure the possibility to exist multipath caused by the corona noise generated in high voltage electric lines recepting GNSS signals. Experiments were realized with a 69 kV tension electric line localized in Santa Maria/RS. A serie was located with eleven transversal points to the longitudinal ranging of the transmission line. In this points, the eletromagnetic field was estimated using an equipment to measure the electromagnetic field EM-8000 model. Valuations was realized about the interferences on positioning by the absolut method, using a GNSS receiver with C/A code Garmin GPS II Plus model and the positioning by the relative method with the GNSS receiver L1/L2 Topcon Hiper model. To estimate the interference in the points was necessary to obtain the geodesic coordinates of this points without multipath possibilities caused of corona noise. For this was implanted a squared topographical polygonal where the support points were located far from the transmission lines, free of the electromagnetic field influence. Calculating the variances among the coordinates was necessary transform the geodesic coordinates obtained at GNSS receivers to the Local Topographic System, to make the systems compatible, using the rotation and translation model. Calculating was possible conclude that to the raising method and the geodesic equipment used in this experiment, in a 69 kV transmission line, the found discrepancies were in the standard deviation of 17,10 mm admitted to equipment GNSS receiver L1/L2 and 15 mm to GNSS receiver C/A code, in a 95% confidence level. So it was not evidenced interferences in the electromagnetic field at GNSS signal reception.